Improving Academic Writing Competence of English Education Students through Peer Review and Writing Consultation - Rahmat Huda; Wulan Suci Ramadani; Lili Herawati Parapat (PANTAK: Jurnal Penelitian Tindakan Kelas, 2026)
Academic writing competence is an essential skill for English Education students; however, many students still experience difficulties in developing well-organised, coherent, and academically appropriate texts. Limited writing practice, insufficient feedback opportunities, and challenges in revising written work remain common problems in higher education writing contexts. This study aimed to investigate the improvement of academic writing competence among English Education students through the implementation of peer review and writing consultation activities in the Writing Clinics course. The study addressed the need for an integrated writing support approach that combined collaborative feedback and individual guidance to enhance students’ writing development.This study employed a Classroom Action Research design involving 19 sixth-semester students of the English Education Study Program. Data were collected through students’ writing assessments, including quizzes, assignments, practical activities, mid-term examinations, and final examinations. The collected data were analysed using descriptive statistical analysis to identify students’ academic writing achievement after participating in peer review and writing consultation activities.The findings showed that students demonstrated satisfactory academic achievement after the implementation of the writing activities. All participants successfully achieved the expected learning outcomes, with final scores ranging from 84 to 90. The results indicated that continuous writing practice, peer feedback, and writing consultation supported students in developing their academic writing competence. This study implied that integrating collaborative and individual feedback strategies could provide an effective learning environment for improving academic writing skills among English Education students. The findings contributed to writing pedagogy by highlighting the importance of feedback-based instruction in supporting students’ academic writing development.